Surgical treatment of melanoma metastases to the small bowel: A single cancer referral center real-life experience. Issue 2 (February 2021) - Gallino, Gianfranco; Maurichi, Andrea; Patuzzo, Roberto; Mattavelli, Ilaria; Barbieri, Consuelo; Leva, Andrea; Valeri, Barbara; Cossa, Mara; Galeone, Carlotta; Pelucchi, Claudio; Santinami, Mario
Abstract: Introduction: Treatment of metastatic melanoma has rapidly changed during the last years, and patients often require a multidisciplinary approach to achieve effective results. We aimed to assess the survival benefit achieved through surgical approach to patients with small bowel (SB) metastases from cutaneous melanoma, to emphasize the potential role of surgery in association with novel therapies. Methods: Ninety consecutive patients with cutaneous melanoma diagnosed as having resectable SB metastases from 1995 to 2015 were retrospectively investigated. Results: Median age at surgery of melanoma metastases was 53.4 years. Among 30 patients who had a curative-intent resection, the 5- and 10-year survival rates were 61% and 54%, respectively, while among 60 patients treated with a palliative surgery the corresponding rates were both 4%. Among 29 patients, for whom the interval time between the occurrence of SB metastases and the previous surgical event on GI tract was ≥36 months, the 5-year overall survival rate was 42%; for 56 patients who had an interval time <36 months the corresponding survival rate was 14%. Within the whole series, an absence of any residual disease after surgery (R0) was a factor affecting better survival, regardless of the evidence of metastases in other organs. Conclusion: Our observational data showed that surgical treatment for patients with SB metastases from melanoma might increase survival, but further studies are needed to confirm this finding. In the age of novel available therapies, the increase in survival time given by surgery may offer important chances for patients to benefit from systemic therapies.